2021
DOI: 10.1186/s12870-021-03289-8
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-wide N6-methyladenosine (m6A) methylation in watermelon under CGMMV infection

Abstract: Background Cucumber green mottle mosaic virus (CGMMV) causes substantial global losses in cucurbit crops, especially watermelon. N6-methyladenosine (m6A) methylation in RNA is one of the most important post-transcriptional modification mechanisms in eukaryotes. It has been shown to have important regulatory functions in some model plants, but there has been no research regarding m6A modifications in watermelon. Results We measured the global m6A le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 76 publications
0
23
0
Order By: Relevance
“…It has been suggested to be part of a novel antiviral system because genetic depletion of a plant m 6 A demethylase negatively affects alfalfa mosaic virus accumulation and movement (Martínez‐Pérez et al, 2017, 2021). The overall plant m 6 A level has been reported to be altered by RNA viruses of the genera Tobamovirus , Bymovirus, Tenuivirus , and Fijivirus (He et al, 2021; Li et al, 2018; Zhang, Zhuang, et al, 2021; Zhang, Wang, et al, 2021). Despite these recent studies, the biological significance of internal RNA methylation and m 6 A in plant virus infection and antiviral immunity is poorly understood.…”
Section: Figurementioning
confidence: 99%
“…It has been suggested to be part of a novel antiviral system because genetic depletion of a plant m 6 A demethylase negatively affects alfalfa mosaic virus accumulation and movement (Martínez‐Pérez et al, 2017, 2021). The overall plant m 6 A level has been reported to be altered by RNA viruses of the genera Tobamovirus , Bymovirus, Tenuivirus , and Fijivirus (He et al, 2021; Li et al, 2018; Zhang, Zhuang, et al, 2021; Zhang, Wang, et al, 2021). Despite these recent studies, the biological significance of internal RNA methylation and m 6 A in plant virus infection and antiviral immunity is poorly understood.…”
Section: Figurementioning
confidence: 99%
“…In watermelon, the infection by cucumber green mottle mosaic virus (CGMMV) leads to the decrease in global m 6 A level and the increase in expression of m 6 A demethylase gene ClALKBH4B (He et al, 2021). Some m 6 A-modified transcripts related to plant immunity display altered m 6 A enrichments and transcript levels in response to CGMMV infection.…”
Section: Regulation Of the Biotic Stresses In Cropsmentioning
confidence: 99%
“…In addition, when the m 6 A methyltransferase genes LsMETTL3 and LsMETTL14 from small brown planthopper (SBPH), the insect vector of RBSDV, were silenced, the titre of RBSDV in the midgut cells of SBPHs increased significantly, suggesting a negative correlation between the overall m 6 A levels and the virus replication (Tian et al ., 2021 ). In watermelon, the infection by cucumber green mottle mosaic virus (CGMMV) leads to the decrease in global m 6 A level and the increase in expression of m 6 A demethylase gene ClALKBH4B (He et al ., 2021 ). Some m 6 A‐modified transcripts related to plant immunity display altered m 6 A enrichments and transcript levels in response to CGMMV infection.…”
Section: Regulatory Mechanisms Of M 6 a On Crop St...mentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, it has been shown that the m 6 A-level is reduced after TMV infection in Nicotiana tabacum plants . In watermelon, global m 6 A levels are reduced in response to cucumber green mottle mosaic virus (CGMMV) infection implying that a global hypomethylation of m 6 A likely activates watermelon defense responses early in CGMMV infection (He et al, 2021). Furthermore, infected plants showed…”
Section: A In Plant Viral Infectionsmentioning
confidence: 99%